The unfolding of gender disparity in literacy: Block-wise evidences from Kannauj district, Uttar Pradesh - Shreyanshi Shukla; Seema Tiwari (National Geographical Journal of India, 2022)
Despite a sharp increase in female enrolment at various levels of education, the gender gap in education remains a topic of concern in developing countries. As per the 2011 Census enumeration, India has an overall literacy rate of 74 percent, with a gender differential of 16.30 percent. In the same Census, the respective literacy in the Kannauj district was 72.70 percent in total, with female literacy at 63.33 percent and male literacy at 80.90 percent. The result shows a significant gender gap in literacy levels, both at the national as well as district levels. This paper aims to map, block-wise gender disparity in literacy in the Kannauj district. This study is based on secondary data obtained from the Census of India, 2001-2011. Sopher’s Disparity Index (SDI) method has been used to compute the block-wise gender differential in literacy in the district. Outcomes of the study reveal that rural areas are more susceptible to gender differential in comparison to that urban areas. To overcome the gender gap in literacy and improve the literacy of the district, the study recommends the provision of an effective adult-literacy program in rural areas with more attention on school dropouts and females of the above thirty age group.